Correlation between Severity of Diarrhea and Blood Sodium Levels in Adult Patients with Acute Gastroenteritis at Manado Adventist Hospital North Sulawesi - H.W. Paulus, Syalomitha; S. Purwanto, Diana; H.M. Kaligis, Stefana (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Acute gastroenteritis has become a leading cause of global mortality, with approximately 41 million deaths each year, about 85% of which occur in low- and middle-income countries. Acute gastroenteritis is often associated with the severity of diarrhea, which serves as a primary indicator in its management, particularly concerning blood sodium levels. Objective: The aim of this study is to determine the relationship between the severity of diarrhea and blood sodium levels in adult patients with acute gastroenteritis at Advent Hospital Manado, North Sulawesi. Methods: This study employs an analytical observational design with a retrospective cross-sectional approach. Secondary data were obtained from patient medical records. A total sampling method was used, resulting in 249 samples that met the inclusion and exclusion criteria, along with vesikari scoring. Results and Discussion: Based on the study results, 196 (78,7%) patients had normal sodium levels, with the majority experiencing moderate diarrhea severity, accounting for 126 (50,6%) patients. The results of the Chi-square test analysis show that p-value=0,320. Conclusion: There is no correlation between the severity of diarrhea and blood sodium levels in adult patients with acute gastroenteritis at Advent Hospital Manado.